Supervision the Management of Holding Company Gowa Mandiri in Gowa Regency, South Sulawesi Province - Sjafrudin Mosii; Asep Sumaryana; Bahrullah Akbar; Sinta Ningrum (Universitas Padjadjaran, 2021)
The objective of this research aimed to study and analyze the main problem, the root cause of the problem, the conceptual model of control and designing the action plan for the transformation of the municipally-owned corporations (MOC) at PD Holding Company Gowa Mandiri with research period from 2013 to 2018. This research utilize qualitative analysis using Soft System Thinking (SST) approach and Soft System Methodology (SSM) method. The primary data gathered from the interview and focus group discussion with focal points. I find two main problems in the MOC which is the lack of Good Corporate Governance (GCG) and interventions from the local government. There are also 11 root causes of the main problem. I suggest that MOC need a strengthened regulation on GCG and enhancing the paradigm of the local government to view MOC as a strategic organization so as to improve the policy making process of the MOC.